2014
DOI: 10.1103/physrevb.89.155435
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of Dirac electrons in graphene quantum dots

Abstract: We observe spatial confinement of Dirac states on epitaxial graphene quantum dots with low-temperature scanning tunneling microscopy after using oxygen as an intercalant to suppress the surface state of Ir(111) and to effectively decouple graphene from its metal substrate. We analyze the confined electronic states with a relativistic particle-in-a-box model and find a linear dispersion relation. The oxygen-intercalated graphene is p doped [E D = (0.64 ± 0.07) eV] and has a Fermi velocity close to the one of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 36 publications
8
44
0
Order By: Relevance
“…302 In a recent experiment, the graphene was intercalated by oxygen in order to exclude the influence of surface states of the iridium. 304 Interestingly, one experiment also showed that the modulation of the LDOS did not depend on the type of the edge. 301 …”
Section: Cvd Grown Graphene Islandsmentioning
confidence: 94%
See 1 more Smart Citation
“…302 In a recent experiment, the graphene was intercalated by oxygen in order to exclude the influence of surface states of the iridium. 304 Interestingly, one experiment also showed that the modulation of the LDOS did not depend on the type of the edge. 301 …”
Section: Cvd Grown Graphene Islandsmentioning
confidence: 94%
“…[300][301][302][303][304] Besides mapping the topology of the graphene islands, the local density of states (LDOS) was probed as a function of position. [300][301][302][303][304] A modulation of the LDOS with position and dot geometry was found and interpreted as influences from quantum confinement 300,301,303,304 or as the observation of the wave function. 302 In a recent experiment, the graphene was intercalated by oxygen in order to exclude the influence of surface states of the iridium.…”
Section: Cvd Grown Graphene Islandsmentioning
confidence: 99%
“…Modifying the properties of Gr/Ir(111) by intercalation of atoms or molecules has been proven to be a straightforward and versatile concept. 7,18 Third, oxygen intercalation, with oxygen strongly bound to the substrate, effectively decouples Gr from its substrate, making its properties very close to those of freestanding Gr. First, oxygen has the potential to strongly interact with Gr under a variety of conditions leading to processes like combustion 16 or graphene oxide formation.…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate this, consider a hypothetical graphene electron that is stripped of its spinor structure and instead has a scalar wavefunction. Such a particle would mimic a massless, spinless particle, and thus could be described by the Klein-Gordon equation 9 , which has effectively described finite-sized GQD islands [30][31][32][33] . In similar fashion to our previous Dirac calculations, we solve the Klein-Gordon equation in the presence of a potential step (Supplementary Information) for the GQD in Fig.…”
mentioning
confidence: 99%
“…This is the first reported visualization of quasi-bound Dirac electrons at sharp, step-potential n-p junctions. Previous STM experiments have studied finite-sized patches of chemical vapour deposition (CVD)-grown GQDs on the surface of Ir(111) [30][31][32][33] . We stress that the origin of the quantized states in these prior studies is due to quantum size effects from the finite extent of the graphene flake.…”
mentioning
confidence: 99%